Geobios - Geobios (Elsevier, 2026)
Geobios publishes bimonthly in English original peer-reviewed articles of international interest in any area of paleontology, paleobiology, paleoecology, paleobiogeography, (bio)stratigraphy and biogeochemistry. All taxonomic groups are treated, including microfossils, invertebrates, plants, vertebrates and ichnofossils. Geobios welcomes descriptive papers based on original material (e.g. large Systematic Paleontology works), as well as more analytically and/or methodologically oriented papers, provided they offer strong and significant biochronological/biostratigraphical, paleobiogeographical, paleobiological and/or phylogenetic new insights and perspectices. A high priority level is given to synchronic and/or diachronic studies based on multi- or inter-disciplinary approaches mixing various fields of Earth and Life Sciences. Works based on extant data are also considered, provided they offer significant insights into geological-time studies.
FI 0.86
Q2
Keywords: Earth; Space & Environmental Sciences; Paleontology; Paleobiology & Geobiology; Paleontología; Paleobiología; Geobiología; Acuerdos transformativos; Transformative agreements; Paleoecología; Paleobiogeografía; Biogeoquímica; Microfósiles; Icnofósiles